Induction of type I IFN is a physiological immune reaction to apoptotic cell-derived membrane microparticles - Schiller, Martin; Parčina, Marijo; Heyder, Petra; Förmer, Sandra; Ostrop, Jenny; Leo, Albrecht; Heeg, Klaus; Lorenz, Hanns-Martin; Bekeredjian-Ding, Isabelle (The journal of immunology, 2012)
Membrane microparticles (MMP) released from apoptotic cells deliver signals that secure the anti-inflammatory response beyond the nearest proximity of the apoptotic cell. Plasmacytoid dendritic cells (pDC) are sentinels prepared to detect cellular processes that endanger the organism. They play a key role in the regulation of both pro- and anti-inflammatory immune responses. Based on the assumption that pDC could participate in the initiation of the anti-inflammatory response to apoptotic cells, we investigated the effects of apoptotic cell-derived MMP on human pDC. The results obtained in our experiments confirmed that MMP released from apoptotic cells trigger IFN-α secretion from human pDC. They further suggest that pDC activation results from sensing of DNA contained in MMP. MMP-DNA displays a particularly strong stimulatory activity compared with MMP-RNA and other sources of DNA. Inhibition of MMP-induced IFN-α secretion by cytochalasin D, chloroquine, and an inhibitory G-rich oligodeoxynucleotide identify TLR9 as the receptor for MMP-DNA. In marked contrast to the pDC response in autoimmune patients, in healthy subjects MMP-mediated stimulation of pDC-derived IFN-α was found to be independent of FcγRIIA (CD32A). Based on our findings, we conclude that induction of pDC-derived IFN-α by MMP is a physiological event; future investigations are necessary to elucidate whether pDC activation promotes inflammation or propagates tolerance in the context of apoptotic cell clearance.
Gesehen am 04.05.2018